Pelaksanaan Upaya Hukum Banding Oleh Notaris Atas Putusan Majelis Pengawas Wilayah Provinsi Bali - Chandra Mahayani, Gusti Ayu Indira; Parsa, I Wayan; Sumardika, I Nyoman (Acta Comitas : Jurnal Hukum Kenotariatan, 2018)
The Article 73 (1) (e) of the Law 2/2014 concerning the Amendment of Law 30/2004 on Public Notary (UUJNP), regulates that the Regional Supervisory Council (MPW) has the authority to give sanction to a public notary, either verbally or in written. However, based on the empirical findings, there is a decision of Bali’s MPW that gives temporary suspension to Notary X. This finding, reflects the gap between the theory of law and its actual implementation of a supervisory conduct of the Bali’s MPW, specifically on giving a punishment. The purpose of this study is to critically analyze the legal position of the decision of the Supervisory Board of the Bali Province Region as a decision of the State Administration Officer and Identify the implementation of an appeal by the Notary X on the decision of the Bali Province Regional Supervisory Board. By using the juridic empirical approach, which the primary sources were obtained through indepth interviews with interviewees and the secondary sources of data were obtained through library research on primary, secondary, and tertiary source of law. This research shows that the appeal process was effectively conducted as required by the Article 77 UUJNP and Article 33 vide Article 35 Miniter of Law and Human Rights Regulation M.02.Pr.08.10/2004 and the decision’s letter of Bali’s MPW as a state officials could be subjected to a lawsuit by a public notary or any other affected parties to the State Administration Court as an Administrative Dispute. However, until 2018 there are no decisions of Bali Province’s MPW ever being sued to the Administrative Court.